Implementing IFRS in local government: value adding or additional pain - Pilcher, Robyn; Dean, G. (Emerald Group Publishing Limited, 2009)
Purpose – The aim of this paper is determine the impact financial reporting obligations and, in particular, the International Financial Reporting Standards (IFRS) have on local government management decision making. In turn, this will lead to observations and conclusions regarding theresearch question: “Does reporting under the IFRS regime add value to the management of localgovernment?” Design/methodology/approach – Following analysis of a survey instrument distributed to all local governments in all states of Australia, this research reports on interviews within Australia’s largest state – New South Wales (NSW). Findings – In general, findings suggest that for smaller councils and those situated away from the major cities, the time spent on complying with IFRS and various other legislative demands results in management accounting issues often being downplayed. Research limitations/implications – A further paper needs to be conducted in order to determine in the second year of implementation the impact of IFRS – both in Australia and, in the future, in other countries – where local government is implementing IFRS. Practical implications will be evident when all Australian states are compared as NSW is the only state where an IFRS template has been produced for all local authorities. Originality/value – This is the first known analysis of IFRS in local government in Australia, and possibly the world. It utilises both survey and interview instruments within an institutional theory framework to capture the full richness of data available.